GLOBALISASI DAN PERGESERAN DIMENSI BUDAYA LOKAL:TANTANGAN PELESTARIAN NILAI TRADISIONAL - Fadil Mas’ud; Alfret Benu; Desiana M. Bulu; Sonya W. O. Ay; Yosepha N. Gudhu; Irennia S. Nomleni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research examines the impact of globalization on the dynamics of local culture, which has long been an important part of Indonesian identity. The flow of globalization, triggered by advances in communication technology, increased population movement, and the intensity of interaction between countries, has brought about significant changes in cultural values, norms, and practices passed down through generations. This study employed a desk study method, examining various scientific literature discussing the relationship between globalization and culture.The results show that the influence of globalization is evident in three main aspects of culture: communication patterns and social relations, economic and environmental conditions, and the behavioral orientations of the younger generation. These changes are evident in the weakening role of traditional institutions, the decreasing use of regional languages, and the increasing cultural uniformity due to the dominance of global media. Furthermore, the younger generation's interest in traditional cultural activities has also declined due to their increased exposure to global popular culture. These findings underscore the need for strategic and targeted measures to maintain the sustainability of local culture. These efforts include strengthening government policies related to cultural protection, empowering indigenous communities, strengthening local wisdom-based education, and utilizing digital technology to support the promotion, documentation, and preservation of culture to ensure its relevance amidst rapid global change.